POLA PENGEMBANGAN KURIKULUM PESANTREN Kasus Al-Mukhlishin Mempawah Kalimantan Barat - Lailial Muhtifah (Jurnal Pendidikan Islam, 2012)
An educational institution that allows organizing formal and non-formal learning even informal at once is Pesantren. Historically, direct linkages among environment of madrasah, families and communities indeed countries have been held for more than four centuries. Thus, Pesantren needs to formulate a clear curriculum that is able to cover all forms of education and the environment. Actually, those efforts have been made by Pesantren Al Mukhlisin Mempawah West Kalimantan. This investigation aims to describe the pattern of development of the curriculum in Pesantren. It used a case study method. The data were obtained from interviews, observation and document analysis. The results indicate that the development of curriculum in Pesantren should still take into account the quality of the curriculum in the planning, control and reinforcement. The basic character of the curriculum can be based on the character of believers as Ulul albab which historically has been the primary vision of the schools since the 17th century. In addition, the character is intergrated in such a way in the form of Islamic learning, teaching and real-life boarding students, teachers and scholars (parenting boarding school).